1985
DOI: 10.1007/bf00022936
|View full text |Cite
|
Sign up to set email alerts
|

A selection procedure for ear drying-rates in maize

Abstract: Rewiwl 10 April I984 INDEX WORDS Zeamays, maize, ear moisture, dry-down rate. SUMMARY A selection procedure to change the drying rates of maize (Z~LI mays L.) ears was developed and tested. Results indicated that drying rates were affected by hybrid genotype, ear maturity at harvest, number of kernels per row, ear diameter.and moisture content at harvest. Mass selection was initiated in an early synthetic, NDSG, in an attempt to produce both fast and slow drying strains. After two cycles resultant substrains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
0
23
0
2
Order By: Relevance
“…If grain moisture increases, shelling efficiency and grain quality will be reduced and drying costs and shrink age penalties increase (Johnson et al 1963, Sweeney et al 1994. Ear moisture differences at physiological maturity were deemed important (Cross 1985). Selection inbred lines based on low ear moisture at 45 day post-pollination could effectively reduce ear moisture at harvest (Cross et al 1987;Cross and Kabir 1989).…”
Section: Introductionmentioning
confidence: 99%
“…If grain moisture increases, shelling efficiency and grain quality will be reduced and drying costs and shrink age penalties increase (Johnson et al 1963, Sweeney et al 1994. Ear moisture differences at physiological maturity were deemed important (Cross 1985). Selection inbred lines based on low ear moisture at 45 day post-pollination could effectively reduce ear moisture at harvest (Cross et al 1987;Cross and Kabir 1989).…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between late-season drying rate and grain moisture at harvest was reported by Kang and Zuber [56]. Selection of inbred lines based on low GWC at early stages has been proved effective in reducing GWC at harvest [37][38][39].…”
Section: Correlations Among Gwc and Gdr At Different Stagesmentioning
confidence: 87%
“…Besides, low GWC and high Grain Dehydration Rate (GDR) at harvest were very important for maize production in temperate regions (midto short-season areas, such as Huanghuihai maize belt in China), which could facilitate machinery harvest, shelling efficiency, grain quality and reduce additional drying cost and shrinkage penalties [28,[33][34][35][36]. Previous research has shown that selection of inbred lines based on low ear-moisture content at a given date after pollination was an effective way to result in low grain moisture content at harvest for inbred lines and associated hybrids [37][38][39]. However, QTL mapping for grain water relations had been reported mostly for Grain Water Content at harvest [21,36,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Ear weight (EW) is a very important trait in maize (Zea mays L.) breeding programs related to yield (Cross, 1985), but at present, a maize germplasm with high EW is quite lacking. To resolve this problem, an effective solution is to utilize elite genes associated with EW to improve the trait.…”
Section: Introductionmentioning
confidence: 99%